THE IMPACT OF ROLE-PLAY TECHNIQUE ON THE STUDENTS’ ENGLISH SPEAKING SKILL - Nichella Ayu Clarita; Indah Rahmawati; Solikin Sudibyo (Universitas Islam Negeri Alauddin Makassar, 2020)
Many students usually find it hard to speak in English, because they have not practiced enough. This reason makes them cannot speak English well. Speaking is the skill which student should master it in order to communicate with other people. The situation in the learning process is one of the important things that the teacher should consider. This research aims to know; (1) the students’ achievement of the third semester of English Education Department at the University of Technology Yogyakarta in speaking English using role-play technique on academic year 2018/2019, and (2) the influencing factors to the students’ speaking skill achievement using role-play technique. The method used was quantitative method with experimental design to 9 students as the research sample. The data were analysed using Microsoft Excel 2013. The findings indicated that the mean score increased from 70 to 78.88, the standard deviation also improved from 6.123 to 7.817. Furthermore, the data from questionnaire indicated that the students had positive responses toward the use of role-play technique. Therefore, the use of role-play technique can improve the students’ speaking ability at this experimental research.